Prof. N. N. Glubokovsky and His Influence on the Biblical Studies in Bulgaria - Traychev, Emil (Forum Theologicum Sardicense, 2025)
Emil Traytchev Stoyanov, Prof. N.N. Glubokovsky and His Influence on the Biblical Studies in BulgariaThe influence of N. N. Glubokovsky‘s work on New Testament studies in Bulgaria is evident both historically and currently. In the past, scholars such as Prof. H. Giaurov, Associate Prof. Archimandrite Ser-gius (Yazadzhiev), and Prof. Ivan Dimitrov were significantly impacted by his contributions. Today, this influence continues with scholars like Prof. Emil Traychev, Head Assist. Pavel Subev, Father Theodore Stoychev, and others. Notably, at the end of his life, Prof. Glubokovsky recognized Prof. Hristo N. Giaurov as „the best and most prolific Bulgarian New Testament scholar of the 20th century.“ In this paper, I will provide a few examples illustrating Glubokovsky‘s impact on two main areas of New Testament academic study: 1) New Testament Introduction and 2) New Testament Interpretation.